KETERAMPILAN MENULIS ILMIAH MAHASISWA PESISIR JAWA TENGAH (Survai di Universitas Pekalongan Tahun Akademik 2014/2015) - Chamdi Rochmat; Hanindya Restu Aulia; Afrinal Pramitasari (LPPM Universitas Pekalongan, 2015)
The aims of this study was to describe the writing skills of student thesis coast of Central Java and describe the factors that affect the student thesis writing skills coast of Central Java. The method Having used was is descriptive survey method. This research was conducted at the University of Pekalongan academic of 2014/2015 for six months. Was collected by questionnaire technique and read&record techniques. Results of the analysis of the validity of the statement questionnaire with product moment formula of 40 point statement showed that there were 36 items declared valid, otherwise invalid while there were four items for validity coefficient delede smaller than r-critical, ie 0.36 (n = 30 degree real 0.05). Meanwhile, the reliability test questionnaire which Alpha Cronbach reliability coefficient generated value of 0.93 which means that the questionnaire stated reliable. Data were analyzed using statistical questionnaires and then interpreted descriptively. Based on the results that the students' skills of coastal Central Java, particularly the University of Pekalongan in scientific writing (thesis) by applying the rules of Indonesian was good and right is still lacking. Lack of ability is manifested in the discovery of errors in spelling, diction errors, and errors in the preparation of students who studied sentence. The factors that lead to low scientific writing skills (thesis) students include: (1) in a particular faculty, counselors and testers thesis questioning not so technical matters related to the language problem, (2) on the Indonesian lectures at certain faculties, content lecture materials that can train students to write well is still limited, (3) a lot of students who do not care about aspects of language that has been determined. in practice the writing.